DEVELOPMENT OF MATHEMATICAL CONNECTION TEST ON SOCIAL ARITHMETIC MATERIALS FOR STUDENTS’ JUNIOR HIGH SCHOOL - Wina Desthiani; Nur Izzati (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2022)
This study aims to find out the procedure and assess the quality of developing test instruments to measure students' mathematical connection abilities. Students seemed lacking in answering questions to develop their mathematical connection ability, therefore it is necessary to practice questions to measure students' mathematical connection abilities. This research is a research and development research and development under formative research model that conducted through four sreps. The data collection instruments in this study were validation sheets and test instruments. The test subjects in this study were 10 students. The results obtained from the content validity test were declared valid because the CVR and CVI values were 1 which refer to very appropriate categories. The reliability of the instrument is declared reliable, where the reliability value is 0.815 which referred to a high reliability or consistency interpretation. Meanwhile, in terms of difficulty level, the average total score is 0.36 in the intermediate category. In terms of discriminating power, the average total score is 0.40 which refer to the good category. Thus, the developed mathematical connection ability test instrument has fulfilled to be a good quality.